Determinant Factors of COVID-19 Vaccination Participation at Ndetundora Health Center, Ende, East Nusa Tenggara - Hafaf Lutfiani Sani; Muntasir; Tadeus A. L. Regaletha (Journal of Health Promotion and Behavior, 2023)
Background: The COVID-19 pandemic is one of the major public health problems today and the whole country is experiencing a pandemic. Vaccination is the government's effort to tackle the COVID-19 pandemic. The coverage of COVID-19 vaccination at the Ndetundora Health Center in 2021 is still low, namely as much as 14.80% for dose 1 and 7.04% for dose 2, then in 2022 the vaccination coverage will increase quite high, namely 75.16% for dose 1 and 53.23% for dose 2. The purpose of this study was to find out the public's interest in taking the COVID-19 vaccination in the working area of the Ndetundora Health Center, Ende Regency in 2022. Subjects and Method: A cross-sectional study was conducted at the Ndetundora Health Center, Ende, East Nusa Tenggara, from September to October 2022. A total of 243 people were selected for this study. The dependent variable was the public's interest in taking the COVID-19 vaccination. The independent variables are age, gender, education, occupation, knowledge, attitude, community motivation and public communication. Data were collected using a questionnaire and analyzed using Chi-square. Results: The results showed that someone with higher education increased their interest in taking the COVID-19 vaccination by 0.38 times compared to people with low education, and the results were statistically significant (OR= 0.38; 95% CI= 0.21 to 0.69; p= 0.001). Someone with motivation High motivation increase interest in taking the COVID-19 vaccination by 49.5 times compared to those with low motivation (OR = 49.5; 9% CI = 21.49 to 114.16; p < 0.001), good public communication will increase public interest in taking the COVID-19 vaccination 2.74 times compared to poor public communication (OR= 2.74; 95% CI= 1.20 to 6.25; p= 0.014). Conclusion: Education, knowledge, attitudes, community motivation, and public communication have a significant effect on participation in the COVID-19 vaccination. Keywords: public interest, vaccination, COVID-19. Correspondence: Hafaf Luthfianti Sani. Study Program of Public Health, Faculty of Public Health, Universitas Nusa Cendana. Jl. Adisucipto, Penfui, Kupang, 85001, East Nusa Tenggara. Email:  hafafsani16@gmail.com. Mobile: +62 821-4436-7462.